Phytochemical Characterization of Wild Hops (Humulus lupulus ssp. lupuloides) Germplasm Resources From the Maritimes Region of Canada - McCallum, Jason L.; Nabuurs, Mark H.; Gallant, Spencer T.; Kirby, Chris W.; Mills, Aaron A. S. (Frontiers in Plant Science, 2019)
A survey was conducted in the Maritimes region of eastern Canada to measure the phytochemical diversity of prenylchalcone, soft resins (alpha & beta acids), and flavonol constituents from 30 unique wild-growing populations of hops (Humulus lupulus L.). Based on cone chemometrics, the majority of accessions (63.3%) are native Humulus lupulus ssp. lupoloides, with cones containing both xanthogalenol and 4’-O-methyl xanthohumol as chemotaxonomic indicator molecules. Interestingly, the leaves of all verified Humulus lupulus ssp. lupulus accessions accumulated high proportions (>0.20 total flavonols) of two acylated flavonol derivatives (kaempferol-3-O-(6’’-O-malonyl)-β-D-glucopyranoside; quercetin-3-O-(6’’-O-malonyl)-β-D-glucopyranoside), both previously unreported from hops leaves. The native lupuloides accessions examined possess only trace amounts of this compound in their leaves (<0.10 total flavonols), suggesting its potential utility as a novel, leaf-derived chemotaxonomic marker for subspecies identification purposes. A leaf-derived taxonomic marker is useful for identifying wild-growing accessions, as leaves are present throughout the entire growing season, whereas cones are only produced late in summer. Additionally, the collection of cones from 10-meter tall wild plants in overgrown riparian habitats is often difficult. The total levels of alpha acids, beta acids, and prenylchalcones in wild-collected Maritimes lupuloides cones are markedly higher than those previously reported for lupuloides individuals in the westernmost extent of its native range and show potentially valuable traits for future cultivar development, while some may be worthy of immediate commercial release. The accessions will be maintained as a core germplasm resource for future cultivar development.